Simultaneous Determination of Sodium Benzoate and Potassium Sorbate Preservatives in Foodstuffs Using High Performance Liquid Chromatography - Antakli, S.; Alahmad, A.; Badinjki, H. (Asian Journal of Chemistry, 2010)
A reversed-phase high-performance liquid chromatography (HPLC) analysis without preextraction was carried out for rapid determination of sodium benzoate and potassium sorbate which were added as preservatives to different samples commercially available in Syrian Arab Republic local markets such as tomato sauce, soft drink, beverages and energy drink. Separation and determination of sodium benzoate and potassium sorbate were performed on a 5 μm Purospher® STAR RP-18 column (25 cm × 4.6 mm), using caffeine as an internal standard (0.04 mg/mL), with UV detection at 235 nm. The column temperature was 40 °C. Mobile phase was (acetate buffer and methanol) with percentage (25:75), at a flow rate 1.2 mL min-1, The injection volume was 20 μL. The two elution peaks were completely separated with a good resolution. This method has offered a determination of sodium benzoate and potassium sorbate directly with a high accuracy and authenticity for the results without extraction need.